Фестивалі Карпатського регіону як чинник розвитку етнотуризму - Бучко, Жанна (Львів: ЛІЕТ, 2011)
Розглянуто фестивалі як вид організації дозвілля та відпочинку туристів. Проаналізовано чинники, за якими можуть класифікуватися фестивалі; здійснено класифікацію фестивалів. Такий підхід до поняття фестивального туризму дозволить розширити існуючі види туризму, розробити концепцію подальшого розвитку туризму та місця фестивалів в економіці регіонів, де вони проводяться.
FESTIVALS OF CARPATHIANS REGION AS FACTOR OF ETNOTOURISM DEVELOPMENT
There are festivals as a form of recreation and leisure at the tourist market. In this article considered the whole set of factors, which may be classified festivals; done typing festivals, a classification scale of festivals. This approach to the concept of festival tourism will enhance the existing forms of tourism, developed the concept further development of tourism and a place of festivals in the economy of regions where they occur.
Keywords: Фестиваль; Туризм; Етнотуризм; Фестивальний туризм